Parental Involvement in Discipline Management of Special Education Students in Schools - Mohamad Salleh, Norshidah; Rosli, Fatin Nabihah (International Journal of Academic Research in Progressive Education and Development, 2019)
This working paper discusses research findings related to parental involvement in the management of discipline among special education children in schools. Its two specific objectives are identifying in this research; the forms of involvement and the obstacles faced by parents. Quantitative research was conducted in survey manner on parents of special needs children in 11 primary schools from a state in Peninsular Malaysia, namely Negeri Sembilan. The research instrument used was questionnaire that was adapted from the questionnaire Family Involvement Study High School. The study sample consisted of 110 parents selected through Purposive Sampling, whereby all parents were identified as having learning difficulty children in primary schools in Negeri Sembilan. Data was analyzed descriptively using SPSS to obtain Mean Values and Standard Deviation. Research findings indicate that the overall involvement of parents in discipline management of special education students was at a moderate level (mean = 3.66). Out of the six forms of parental involvement, the role of parents (mean = 3.90) and study support at home (mean = 4.06) occupied top spots. Meanwhile obstruction to parental involvement in discipline management in schools was also at moderate level (mean = 3.20), where in five of the obstacles were at moderate levels. Socioeconomic standard, however was not a primary obstacle, and was at a low level (mean = 2.58). Thus, problems encountered by these parents need to be handled so that parental involvement with regards to their children’s discipline management can be elevated to a higher level. The implication of this study speaks of the need by school authorities to reduce resistance faced by parents so that they can involve themselves in all activities and programs that are carried out by school. Through the cooperation forged between teachers and parents, misconduct and discipline problems of students can be handled collectively by both school and parents.